Studi Numerik Pengaruh Geometri dan Desain Diffuser untuk Peningkatan Kinerja DAWT (Diffuser Augmented Wind Turbine) - Adhana Tito Hary Wibowo; Ruri Agung Wahyuono; Gunawan Nugroho (Institute of Research and Community Outreach, Petra Christian University, 2013)
Numerical study was conducted on the effect a variation of flange angle on diffuser DAWT performances using Computational Fluid Dynamics (CFD). This research objective is to perform and analyze the flow characteristics such as Velocities profile and static pressure profile on the effect of diffuser’s flat flanged tilt angle. Verification of computation condition result by comparing data qualitative data and quantitive data Ohya’s experiment, (2008). Qualitative analysis showed by velocity contour, streamline contour and velocity vector. Quantitative result showed by the velocity increased profile and static pressure profile graph. The streamline of simulation result showed the bigest blockage effect due to of airflow is flange with angle 900. This effect caused the vortex formation at back side of flange. Velocity vector contour given prediction on direction of stream flow tip losses reduction at the backside of flanged diffuser. Quantitative data showed flow performance in interior diffuser with top increased velocity augmentation of flanged diffuser is angle 900 by 9,82 m/s or 1,96 times freestream velocities and static pressure coefficient value by -2.85.